Problems of Supevision of Buying Circulations Medicine Online - Dewiwaty Dewiwaty; Iriansyah Iriansyah; Bagio Kadaryanto (Unram Law Review, 2021)
Drugs are pharmaceutical preparations that are much needed during the pandemic, such as today. There are so many pharmaceutical preparations circulating through internet-based media, which are not in accordance with applicable regulations so that they have big potential to cause bad impacts. There are various obstacles faced by the government in carrying out supervision of pharmaceutical preparations through the Food and Drug Supervisory Agency, especially related to online drug buying and selling activities. Some of these obstacles include good access to Indonesia's territory, the low level of public knowledge about drugs, low cross-sectoral supervision, and weak legislation. These weaknesses then become a gap for business actors to conduct online buying and selling transactions without complying with applicable regulations. Thus, further supervision is needed by the Food and Drug Supervisory Agency as a form of responsibility and the realization of legal certainty in order to improve justice and public safety as consumers.